2016
DOI: 10.1016/j.ddmod.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling to improve treatments for essential tremor

Abstract: Essential tremor (ET) is a neurological disorder of unknown etiology that is typically characterized by an involuntary periodic movement of the upper limbs. No longer considered monosymptomatic, ET patients often have additional motor and even cognitive impairments. Although there are several pharmacological treatments, no drugs have been developed specifically for ET [1], and 30–70% of patients are medication-refractory [2]. A subset of medication-refractory patients may benefit from electrical deep brain sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…To understand effects of non-tremor activity in ET [32], we simulated Poisson-distributed synaptic inputs from cerebellum or possibly cortex that are related to features such as motor adaptation. Our results showed that non-tremor inputs potentiated intrinsic tremor and depressed extrinsic tremor ( Fig.…”
Section: Non-tremor Cerebellar Inputs May Exacerbate Tremor In Vimmentioning
confidence: 99%
See 3 more Smart Citations
“…To understand effects of non-tremor activity in ET [32], we simulated Poisson-distributed synaptic inputs from cerebellum or possibly cortex that are related to features such as motor adaptation. Our results showed that non-tremor inputs potentiated intrinsic tremor and depressed extrinsic tremor ( Fig.…”
Section: Non-tremor Cerebellar Inputs May Exacerbate Tremor In Vimmentioning
confidence: 99%
“…Aside from tonic currents and Poisson-distributed inputs applied to individual cells in the model (see above), externally sourced synaptic inputs were also simulated. To model ongoing, non-tremor inputs that might arise from cerebellum or cortex [32], we simulated additional Poisson-distributed inputs that terminated on AMPA-ergic synapses on the dendrites of the VIM cells. Each event time of the Poisson input consisted of 25 Gaussian-distributed inputs with a 3 ms standard deviation.…”
Section: Additional Inputsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior computational modeling has investigated multiple aspects of the timing of DBS on thalamic cells, including rebound bursting [8,9,26,48], and recent modeling has been focused on understanding tremor frequency oscillations (TFOs) in the VIM and their relation to DBS [27,51]. We recently developed a detailed computational model of a tremor frequency generating network within the VIM to show how network biophysical properties affected tremor and non-tremor activity [27].…”
Section: Introductionmentioning
confidence: 99%